Minimum-Error Splitting Algorithm for a Dual Layer LCD Display-Part I: Background and Theory - Guarnieri, G.; Albani, L.; Ramponi, G. (Journal of display technology, 2008)
A dual layer high dynamic range liquid crystal display (LCD) can be built by stacking two panels one on top of the other. In this way, the dynamic range is theoretically squared and the bit depth is also increased. However, in order to minimize the parallax and reconstruction errors, dedicated splitting algorithms are needed to generate the two images which drive the panels. In this paper, we present an algorithm, based on variational techniques, which seeks the joint minimization of both errors. We propose a simplified visible difference metric that exploits some limitations of the human visual system and can be easily incorporated into an optimization algorithm. The image splitting task is formulated as a quadratic programming problem, which can be efficiently solved by means of appropriate numerical methods. Preliminary tests on medical images showed that the algorithm has good performances and appears robust with respect to the parameter adjustment.